1994
DOI: 10.1126/science.8047886
|View full text |Cite
|
Sign up to set email alerts
|

Control of Topographic Retinal Axon Branching by Inhibitory Membrane-Bound Molecules

Abstract: Retinotopic map development in nonmammalian vertebrates appears to be controlled by molecules that guide or restrict retinal axons to correct locations in their targets. However, the retinotopic map in the superior colliculus (SC) of the rat is developed instead by a topographic bias in collateral branching and arborization. Temporal retinal axons extending across alternating membranes from the topographically correct rostral SC or the incorrect caudal SC of embryonic rats preferentially branch on rostral memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(77 citation statements)
references
References 47 publications
(14 reference statements)
3
74
0
Order By: Relevance
“…It has previously been shown in chick (Walter et al, 1987b), mouse (Godement and Bonhoeffer, 1989), and rat (Simon and O'Leary, 1992;Roskies and O'Leary, 1994) that membranes from posterior tectum/SC will repel retinal axons or inhibit their branching in a topographically specific manner and that ephrin-A2 and ephrin-A5 are sufficient for this activity in vitro (Nakamoto et al, 1996;Monschau et al, 1997). EphA receptors are predicted to be involved in the response, based on several lines of evidence, including retinal expression gradients (Cheng et al, 1995;Feldheim et al, 1998Feldheim et al, , 2000Brown et al, 2000), the addition of soluble ligand or receptor fusion proteins in vitro (Ciossek et al, 1998), antibody or dominant-negative inhibition in vitro of chick EphA4, a receptor that is not graded but seems to be involved in retinal responses (Walkenhorst et al, 2000), and ectopic expression of EphA3 in mouse retina (Brown et al, 2000).…”
Section: Effect Of Epha5 Mutation On Response To Repellent Activity Imentioning
confidence: 94%
“…It has previously been shown in chick (Walter et al, 1987b), mouse (Godement and Bonhoeffer, 1989), and rat (Simon and O'Leary, 1992;Roskies and O'Leary, 1994) that membranes from posterior tectum/SC will repel retinal axons or inhibit their branching in a topographically specific manner and that ephrin-A2 and ephrin-A5 are sufficient for this activity in vitro (Nakamoto et al, 1996;Monschau et al, 1997). EphA receptors are predicted to be involved in the response, based on several lines of evidence, including retinal expression gradients (Cheng et al, 1995;Feldheim et al, 1998Feldheim et al, , 2000Brown et al, 2000), the addition of soluble ligand or receptor fusion proteins in vitro (Ciossek et al, 1998), antibody or dominant-negative inhibition in vitro of chick EphA4, a receptor that is not graded but seems to be involved in retinal responses (Walkenhorst et al, 2000), and ectopic expression of EphA3 in mouse retina (Brown et al, 2000).…”
Section: Effect Of Epha5 Mutation On Response To Repellent Activity Imentioning
confidence: 94%
“…Developmental biology studies have highlighted the importance of branch formation during establishment of connections in the nervous system [21][22][23][24]. Further research on axonal extension has shown that the primary growth cone is responsible for delineating future branch points along the axon [25].…”
Section: Discussionmentioning
confidence: 99%
“…These factors may, in addition or alternatively, lead to a selective stabilization of axon terminals in vivo (Simon and O'Leary, 1992a,b;Roskies and O'Leary, 1994;Simon et al, 1994). The observations made with the modified version of the stripe assay presented here or with the "crossed version" of the stripe assay used by O'Leary and coworkers both suggest that the combination of repulsive and adhesive or attractive factors work together in establishing a topographic order in the retinotectal system.…”
Section: Discussionmentioning
confidence: 74%
“…To analyze the role of putative molecules involved in axonal guidance and target recognition, Walter et al (1987a) developed an in vitro assay (stripe assay). In this assay, retinal axons were grown on carpets, which consist of alternating stripes of membranes derived from anterior and posterior embryonic tectum (Walter et al, 1987a,b).In all tested species (chick, mouse, fish, and rat), temporal retinal axons avoid growing on membrane stripes from the posterior SC, whereas nasal retinal axons did not show a growth preference (Walter et al, 1987a,b;Godement and Bonhoeffer, 1989;Vielmetter and Stuermer, 1989;Roskies and O'Leary, 1994). Using this assay, two different membrane-bound putative guiding molecules were identified in the chick, both of which are likely to be involved in steering retinal axons on the chick tectum (Stahl et al, 1990;Drescher et al, 1995): one repulsive guidance molecule (Stahl et al, 1990) selectively affects the growth of temporal retinal axons, whereas a high dose expression of the other (Drescher et al, 1995) leads to the collapse of both temporal and nasal RGC growth cones.…”
mentioning
confidence: 99%